Analytical determination of homocysteine: a review. - Nekrassova, O; Lawrence, N; Compton, R (2003)
The determination of homocysteine has gained high interest within the biomedical community over recent years as the molecule is an important biomarker for a wide range of diseases. The current report gives a brief overview into the biological significance of homocysteine and a rigorous account of the existing detection protocols for homocysteine in biological fluids, as well as trying to anticipate possible future trends in the development of rapid, low-cost and sensitive assays for its detection.